2019
DOI: 10.22159/ajpcr.2019.v12i3.30741
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Aqueous Extract of Atriplex Halimus L. Against Benzene-Induced Damage on Renal Function and Glomerular Cells in Rats

Abstract: Objective: Benzene (BZ) is an important pollutant compound, present in both occupational and general environment that has been linked to adverse health effect. The aim of the current study was to investigate the curative and preventive effect of Atriplex halimus L. (Ah) extract against BZ-induced nephrotoxicity in rats. Methods: A total of 30 male albino Wistar rats were divided into five groups (n=6): Control, Ah, BZ, AhP+BZ, and BZ+AhC. BZ (100 mg/kg b.w) was added in their drinking water for 15 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Regular sinusoidal structures were reserved. The result of the histologic examination experiment is in concordance with biochemical result, which clearly indicate the hepatoprotective effects provided by plant natural products 21,31 .…”
Section: Discussionsupporting
confidence: 79%
“…Regular sinusoidal structures were reserved. The result of the histologic examination experiment is in concordance with biochemical result, which clearly indicate the hepatoprotective effects provided by plant natural products 21,31 .…”
Section: Discussionsupporting
confidence: 79%
“…Notably, various studies on the use of SB have shown its beneficial potential and harmful effects. [11][12][13][14] However, most of these harmful effects were studies carried out in rats, [15] and mice [11] with concentrations above the recommended doses. The recommended range of SB approved by the Joint Food and Agricultural Organization (FAO)/World Health Organization (WHO) Expert Committee on Food Additives are 0−5 mg/kg body weight [16,17] or 1000 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the histological sections having renal necrosis results showed larger diameter of damaged tissue area of 240.92 µm for group II at 1st week than group II which clearly indicates the side effects of over-dosage of fresh mecobalamin. Moreover, in group III, tissue damage was also observed due to intake of expired vitamin B-12 which not only reflects the biochemical malfunctioning of expired selected vitamin but also depicts role of microbial invasion in physiological system which may enter with expired mecobalamin [12].…”
Section: Discussionmentioning
confidence: 97%